2013
DOI: 10.1093/brain/awt274
|View full text |Cite
|
Sign up to set email alerts
|

Visual activity predicts auditory recovery from deafness after adult cochlear implantation

Abstract: Modern cochlear implantation technologies allow deaf patients to understand auditory speech; however, the implants deliver only a coarse auditory input and patients must use long-term adaptive processes to achieve coherent percepts. In adults with post-lingual deafness, the high progress of speech recovery is observed during the first year after cochlear implantation, but there is a large range of variability in the level of cochlear implant outcomes and the temporal evolution of recovery. It has been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
133
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 61 publications
18
133
3
1
Order By: Relevance
“…They reported lipreading scores improved in males at 2 years after implant, resulting in an insignificant gender difference in the long term. Brain imaging studies have documented the gender difference in showing more diffuse brain activation in females during lipreading tasks and language processing, and it was suggested that females present better predictive and integrative cognitive processes than males [Strelnikov et al, 2013]. Nevertheless, in our study, as in the younger population, gender does not influence cochlear implant speech performance in quiet or in noise [Lazard et al, 2012;Holden et al, 2013].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…They reported lipreading scores improved in males at 2 years after implant, resulting in an insignificant gender difference in the long term. Brain imaging studies have documented the gender difference in showing more diffuse brain activation in females during lipreading tasks and language processing, and it was suggested that females present better predictive and integrative cognitive processes than males [Strelnikov et al, 2013]. Nevertheless, in our study, as in the younger population, gender does not influence cochlear implant speech performance in quiet or in noise [Lazard et al, 2012;Holden et al, 2013].…”
Section: Discussioncontrasting
confidence: 55%
“…In the same group of patients, the analysis of brain activation using a speech-processing task demonstrated strong positive correlations between activity at time of implantation in the occipital cortex involved in visual processing and in the posterior temporal cortex known for audio-visual integration, and the level of auditory recovery, but a negative correlation between superior temporal sulcus activation and cochlear implant outcomes. Authors suggest a synergy between visual and auditory modalities that may facilitate improvement of speech intelligibility after implantation [Strelnikov et al, 2013]. Further studies examining neural plasticity after cochlear implantation in elderly deaf patients are needed to better understand the role of the visual modality in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous postimplant imaging studies have identified subregions which differ in the direction and extent to which crossmodal STC activation to visual speech correlates with CI outcomes (8). Given the limited spatial resolution of fNIRS, it is not possible here to interrogate cortical activation in these individual subregions.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence from a PET study in adult CI users showed that greater activation of auditory brain regions during lip-reading predicted poorer speech understanding abilities with a CI (8) and that this activity reduced from an earlier to a later stage of CI rehabilitation (9). Subsequently, it has been assumed that activation of auditory cortex by visual language can limit its capacity for auditory processing (3) and that a reduction in cross-modal activation of auditory cortex to visual speech after implantation may be crucial for successful hearing restoration (9).…”
mentioning
confidence: 99%
“…This result is consistent with the proposal of Rouger et al that the TVA is 'taken over' by visual speech reading tasks in CI users who do not understand speech well. Strelnikov et al (2013) measured PET resting state activity and activations elicited by auditory and audio-visual speech in CI users soon after implantation and found that good speech understanding after 6 months of implant use was predicted by a higher activation level of the right occipital cortex and a lower activation in the right middle superior temporal gyrus. They suggested that the pre-implantation functional changes due to reliance on lip-reading were advantageous to development of good speech understanding through a CI via enhanced audio-visual integration.…”
Section: Deafness Language and Brain Plasticity: Evidence From Imagimentioning
confidence: 99%